A comparative study on the virulence of entomopathogenic fungi against Trogoderma granarium (Everts) (Coleoptera: Dermestidae) in stored grains rice - Iqbal,J. (2022)
Abstract Entomopathogenic fungi (EPF) now a possible safer microbial control measure that could be considered as a substitute for chemical control of insect pests. Three EPF viz., Metarihizium anisopliae, Isaria furnosoroseus and Beauveria bassiana were evaluated for their virulence against the grubs of Khapra beetle, Trogoderma granarium (Everts) under laboratory conditions. The isolates were applied by two methods viz., diet incorporation and an immersion method with 3rd instar 20 grubs of T. granarium for each. The virulence of EPF was determined using percent mortality. Significantly higher mortality was observed in M. anisopliae applied through immersion (98.33%) and diet incorporation (93.33%) methods followed by B. bassiana (90.83 and 85.83%, respectively). The mortality caused by I. furnosoroseus was statistically lower in immersion and diet incorporation methods i.e. 81.67 and 73.33%, respectively. Based on the immersion method, all EPF were studied for multiple conidial concentration i.e., 1×104, 1×105, 1×106, 1×107 and 1×108 under the same in-vitro conditions. All the isolates were pathogenic to grub of T. granarium at the highest conidial concentration. M. anisopliae was proved the most effective virulent resulting in 98.33% mortality of the pest with LT50 4.61 days at 1 × 108 conidial concentration followed by 90.83 and 81.67 percent mortality with 5.07 and 8.01 days LT50, in the application of B. bassiana and I. furnosoroseus, respectively. M. anisopliae showed higher efficacy and could be considered as promising EPF for the development of myco-insecticides against effective biocontrol of T. granarium.